MODEL KOMPETISI PEMBERDAYAAN DAN PENGEMBANGAN KOMUNITAS HOBI MASYARAKAT SEBAGAI TITIK STIMULUS PERTUMBUHAN PEREKONOMIAN LOKAL - Asmoro, Eddi Indro (Proceeding SENDI_U, 2015)
Phenomena in Indonesian society today is the explosion of interest in the community for precious stones, poultry,fish, plants, animals, and much more. Hobby Value of community could as stimulus point for empowerment andcommunity development based community. Community empowerment is a business community learning effort, sothat they are able to manage and be responsible for program development in the community. Learning isimplemented for capacity development community, where implementation must be adapted to the characteristics andcapabilities of the local community because basically every community is unique.Unfortunately, these communitiestend to be seasonal, but the value that can be captured there is how the management system so that the value ofcommunity specialization occurs continuously. Here the system management becomes important, because ofseasonal activity in the community is actually happening rapid economic turnaround from upstream to downstream.Government intervention and non-governmental parties to manage systems specialization community in society as astimulus point of community development and empowerment is key.The design of this model using literature basedon empirical studies of previous research to strengthen the sides of the economic growth model based onspecialization in the community. The design of this model aims to provide a discourse as a stimulus point of growthof the local economy in the empowerment and development of society without governments role in full.Key words: Model Design, Communities, Interaction Activity, Interaction Impact of activity, Empowerment andDevelopment, Competition, The Role of Government and Non-Government